Association between the BDNF 196 A/G polymorphism and sporadic Alzheimer's disease - Ventriglia, M; Bocchio Chiavetto, L; Benussi, L; Binetti, G; Zanetti, O; Riva, M A; Gennarelli, M (Molecular psychiatry, 2002)
MOLECULAR PSYCHIATRY: (2002) 7, 136-139. DOI: 10.1038/sj.mp.4000952